Dogs infection by Trypanosoma cruzi in São Domingos do Capim, State of Pará, Brazil - Almeida, Vívian Tavares; Kobayashi, Yuri Teichii Da Silva; Roque, André Luiz Rodrigues; Barros, Juliana Helena Silva; De Castro, Larissa Renata Silva; Madeira, Ene Almeida Oliveira; Uzcategui, Ricardo Andres Ramirez [UNESP]; Fernandes, Julio Israel (My University, 2015)
The objective of this study was to determine the presence of Trypanosoma cruzi among dogs naturally infected by it inside four rural communities at the Municipality of São Domingos do Capim located in the Northeastern Pará, Brazil. Blood samples were collected from 113 dogs and 85.7%(30/35) of the serologically positive dogs had their blood re-collected after three months. The diagnosis of T. cruzi infection was performed by: fresh blood examination, hemoconcentration, hemoculture, as well as the serological assays Indirect Immunofluorescence Essay (IFAT) and Imunoenzimatic essay (ELISA). The presence of positive dogs in both serologic tests (IFAT + ELISA) was 31%(35/113), distributed among the four communities as follows: (12/44) Uricuriteua, (19/40) Cezaréia, (1/16) Aliança and (3/13) Catita. None of the samples was positive in the fresh blood examination or hemoconcentration, although it was possible to isolate T. cruzi, DTU TcI in one dog sample during its blood re-collection. These results show how dogs are exposed to the T. cruzi transmission cycle, revealing their importance as sentinels for the presence of this parasite in the studied area.
Dogs infection by Trypanosoma cruzi in São Domingos do Capim, State of Pará, Brazil
Keywords: Chagas disease; Diagnosis; Dog; Natural infection; Occurrence